(untitled) (Experimental biology, 2021)
To expand the range of domestic medicinal plant materials and obtain new herbal remedies, it is important to attract wild flora. One of the newest representatives is Rhodiola Semenovii Boriss. The first stage of the pharmacognostic analysis of the properties of Rhodiola Semenowii (Regel & Herder) Boriss. is the analysis of the rhizome and root, which, according to the literature, contain phenolic glycosides, flavonoids, tannins, essential oils, macro- and microelements, etc. The aim of this study is histochemical analysis and assessment of the anatomical features of the underground organs of Rhodiola semenowii Boriss. The results show that Rhodiola semenowii Boriss has a light yellow rhizome bark which can be seen when the outer bark is scraped off. The study of micropreparations of the rhizome of Rhodiola semenowii Boriss showed that the crust of the parenchyma is loose, uneven, in some areas large. The conducting system of the rhizomes of the bundle structure are located in the center of the root in several rows. A peculiar arrangement of phloem in the form of elongated sections. Radial structure of the root xylem and a single arrangement of vessels in the center of the axial cylinder. The presence of simple starch grains in the parenchymal tissues of the rhizome and root. Parenchymal cells of various structures. We need this analysis for a more detailed study of the accumulation of biologically active substances in the cells of various organs at this stage of the root Rhodiola semenowii